2016
DOI: 10.1097/mnm.0000000000000538
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter evaluation of single-photon emission computed tomography quantification with third-party reconstruction software

Abstract: Reliable and reproducible quantification is essential in many clinical situations. Previously, single-photon emission computed tomography (SPECT) has not been considered a quantitative imaging modality, but recent advances in reconstruction algorithm development have made SPECT quantitative. In this study, we investigate the reproducibility of SPECT quantification with phantoms in a multicenter setting using novel third-party reconstruction software. A total of five hospitals and eight scanners (three GE scann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Hippeläinen et al compared the results of different ordered subset expectation maximization (OSEM) reconstruction algorithms [21] and concluded that alignment was best when the images were corrected for attenuation, scatter, and detector and collimator response. Various SPECT/CT vendors have responded to the increasing need for SPECT quantification and now commercially offer software packages for quantification of several radionuclides including 177 Lu [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Hippeläinen et al compared the results of different ordered subset expectation maximization (OSEM) reconstruction algorithms [21] and concluded that alignment was best when the images were corrected for attenuation, scatter, and detector and collimator response. Various SPECT/CT vendors have responded to the increasing need for SPECT quantification and now commercially offer software packages for quantification of several radionuclides including 177 Lu [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…This study is a considerable step towards standardization of absolute SPECT quantification by investigating the quantitative accuracy of different SPECT/CT systems. The quantitative accuracy of individual SPECT-CT systems was assessed earlier for the GE Discovery NM/CT 670 system [5], the Siemens Symbia Intevo system [44] and the Hermes SUV SPECT quantitative reconstruction algorithm [36]. Although an earlier study by Seret et al [32] also compared the quantitative capabilities of four SPECT/CT cameras, our study included the current state-of-the-art quantitative SPECT/CT systems that enable absolute quantification that were not available at that time.…”
Section: Discussionmentioning
confidence: 99%
“…In a different study [34] in which they compared the same three SPECT/ CT systems, they showed that image resolution is very much dependent on the reconstruction algorithm. In recent years, various SPECT/CT and software vendors have responded to the increasing need for SPECT quantification and now commercially offer software packages for quantification of several radionuclides including 99m Tc, 111 In, 131 I, and 177 Lu [35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…NM images generated by HROD had voxel sizes of 4.42 × 4.42 × 4.42 mm 3 . The SPECT standard uptake value (SUV) option 56 was not available at the time of the study.…”
Section: E2 Hermesmentioning
confidence: 99%